Funções de 1º grau : uma proposta para o 9º ano do ensino fundamental - Bianchetti, Tauana (2016)
The concerns about the difficulties involved in teaching and learning processes of mathematical concepts, especially from the algebraic field, motivated the development of this research, with the theme of 1st degree function in elementary school. Facing several questions that emerge in the classroom, it is defined the following question-synthesis: to what dimension the development of an educational product as a didactic sequence enables the learning of mathematical concepts? Following this question, the objective of this research was to analyze if the meanings related with the subject function of 1st degree, developed through an educational product, were appropriated by the students, throughout social interactions produced by the participants in the teaching-learning process. This research is part of a line of theoretical and methodological fundamentals for the teaching of Science and Mathematics, from the Graduate Program in Science and Mathematics Teaching from University of Passo Fundo, and it follows a qualitative approach, for prioritizing the meanings assigned in the development of a didactic-pedagogic proposal. The objects of this analysis were lesson plans and classes, the teacher-researcher s memories, materials produced by the students and audio recordings from the classes. The foundations were sought mainly resorting authors from the mathematics education area, the didactics of mathematics, Theory Historical-cultural and mathematics itself, which subsidized the planning and development of the dissertation, which includes the educational product. In the analysis it was revealed that the development of educational product enabled interactions between students and also between students and the teacher, contributing to the process of formation of concepts and the teacher-researcher had the opportunity to reflect on her practice in the classroom. Also, the study of the proposals developed in the classroom provides a critical reflection on the role of teacher and the students, contributing to continuing education and professional development.